2013
DOI: 10.5121/ijsptm.2013.2402
|View full text |Cite
|
Sign up to set email alerts
|

YourPrivacyProtector: A Recommender System for Privacy Settings in Social Networks

Abstract: ABSTRACT

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 11 publications
(13 reference statements)
0
14
0
Order By: Relevance
“…Ghazinour et al [5] are interested in the users' personal profiles, users' interests and users' privacy settings on photo albums to see whether they are visible to the public, friends, friends of friends, or on a custom setting. By observing how different users choose their settings on photo albums, the researchers classify them into one of three privacy categories.…”
Section: Recommender Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ghazinour et al [5] are interested in the users' personal profiles, users' interests and users' privacy settings on photo albums to see whether they are visible to the public, friends, friends of friends, or on a custom setting. By observing how different users choose their settings on photo albums, the researchers classify them into one of three privacy categories.…”
Section: Recommender Systemsmentioning
confidence: 99%
“…Ghazinour et al [5] analyze users' data in order to understand their behavior in terms of how they choose their privacy settings. They found that most of the users shared information about their age, gender and education.…”
Section: Recommender Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The algorithm has no access to the context and meaning of tags and no insight into the policy the participant intended when tagging for access control. As a result, some rules appeared strange or arbitrary to the participants, potentially driving them toward explicit policy-based tags like "private" and "public [6].…”
Section: Introductionmentioning
confidence: 99%
“…It naturally learned for a given profile of clients and dole out the protection alternatives. It permits clients to see their present security settings on their interpersonal organization profile, to be specific Facebook, and screens and distinguishes the conceivable protection dangers [16] Alessandra Mazzia presented PViz Comprehension Tool an interface and framework that relates all the more straightforwardly with how clients show gatherings and security strategies connected to their systems. PViz permits the client to comprehend the perceivability of her profile as per consequently developed, characteristic sub-groupings of companions, and at various levels of granularity.…”
Section: Literature Surveymentioning
confidence: 99%